Traumatic Leg Fractures in UEFA Football Athletes: A Matched-Cohort Analysis of Return to Play, Reinjury, Player Retention, and Performance Outcomes. Issue 9 (8th September 2021) - Lavoie-Gagne, Ophelie; Gong, Matthew F.; Patel, Sumit; Cohn, Matthew R.; Korrapati, Avinaash; Forlenza, Enrico M.; Barmonyallah, Moses; Parvaresh, Kevin C.; Wolfson, Theodore S.; Forsythe, Brian
Background: The average professional soccer team experiences 1 to 2 traumatic leg fractures per season, with unknown effects on player performance. Purpose: To (1) determine the rate and time to return to play (RTP) following leg fracture, (2) investigate the rate of reinjury following RTP, and (3) investigate long-term effects that lower extremity (LE) fracture may have on elite soccer player performance. Study Design: Cohort study; Level of evidence, 3. Methods: Using publicly available records, we identified athletes sustaining a traumatic leg fracture across the 5 major European soccer leagues (English Premier League, Bundesliga, La Liga, Ligue 1, and Serie A) between 2000 and 2016. Athletes with leg fracture (femur, tibia, and/or fibula) were matched 1:2 to controls by demographic characteristics and performance metrics 1 season before the index timepoint. Investigations included the RTP rate, reinjury rate, player characteristics associated with RTP within 2 seasons, long-term player retention, performance metrics during the 4 following seasons, and subgroup analysis by player position. Results: A total of 112 players with LE fracture and 224 controls were identified. Players with LE fractures were absent for a mean of 157 days (range, 24-601 days) and 21 games (range, 2-68 games). The rate of RTP within 1 season was 80%, with 4% experiencing subsequent refracture. Injured players remained active in the league at a higher rate than their uninjured counterparts. As compared with controls, injured athletes played 309 fewer total minutes ( P < .05), scored 0.09 more assists per game ( P < .01) 1 season after injury, and scored 0.12 more points per game 4 seasons after injury ( P < .01). Defenders were most affected by an LE fracture, playing 5.24 fewer games ( P < .05), 603 fewer total minutes ( P < .01), and recording 0.19 more assists per 90 minutes of play as compared with controls 1 season after injury ( P < .001). Attackers and midfielders demonstrated no significant difference in metrics after RTP when compared with controls. Conclusion: Most players sustaining an LE fracture returned to elite soccer at the same level after a significant loss of playing time, with a 4% rate of refracture. Player retention was higher for those sustaining an LE fracture versus uninjured controls. Overall, injured players did not experience a decline in performance after recovery from an LE fracture.